Students Learning Motivation and Concepts Understanding of Science through the Use of PhET Interactive Simulations - Citra Dwi Rahayu; Septi Budi Sartika (SEJ (Science Education Journal), 2020)
The purpose of this research is to describe the influence of PhET Interactive Simulations on the motivation of learning and understanding the concept of natural science subject matter. This research is a type of quantitative research with design method using one shot case study design. The population and research sample is grade VIII students of SMP 4 which consists of 1 class. The instruments used in this study are motivational learning questionnaires and concept comprehension tests. The technique of analyzing the data of this study is to use correlation statistics. The results showed there was an influence of PhET Interactive Simulations on learning motivation with a low relationship influence rate of 0.273, there was the influence of PhET Interactive Simulations on understanding the concept of natural science with a low influence level of 0.324, and there was the influence of PhET Interactive Simulations on the motivation of learning and understanding the concept of natural science with a low influence level of 0.122. it can be concluded that PhET Interactive Simulations affects the motivation and understanding of the concept of natural science. Further research is expected to uncover other factors that influence the motivation of learning and understanding student concepts in addition to the use of PhET Interactive Simulations.